ANALISIS KARAKTER ANAK BERKEBUTUHAN KHUSUS PADA PEMBELAJARAN MATEMATIKA PEMULA DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN BUSY BOOK - Lailatun Ni’mah; Adellisa Herawati; Juniar Sandrawati (Universitas Muhammadiyah Surabaya, 2022)
This research is used to examine the character of children with special needs in learning mathematics for beginners using busy book learning media. This study uses a qualitative type of literature study method. The data collection method used in this research is in the form of existing documents. Character education for children with special needs is a conscious and planned effort carried out by schools by giving an award to children with special needs to instill noble values as a form of foundational character for the Indonesian nation, including religious, honest, tolerant, disciplined, hard working, creative, independent, democratic, curious, friendly / communicative, care about the environment and responsibility. Which is in accordance with the type of student's disorder. Qualitative data is data in the form of words, sentences, and pictures in a discussion.Literature study is a series of activities related to the methods of collecting library data, reading and taking notes, and managing research materials. Another understanding of literature study is looking for a theoretical reference that is relevant to the case or problem that has been found. References can be obtained through books, journals, research report articles, and sites on the internet.Â Keywords: The character of children with special needs, busy book media, learning mathematics